Personality Traits and Communication Apprehension: The Role of Neuroticism among Family Planning Counselors - Benedicta Ika Ermadela; Rachmat Kriyantono (Bulletin of Counseling and Psychotherapy, 2026)
This study aims to examine the correlation between the personality dimension of neuroticism and communication anxiety. In the personality dimensions formulated by Eysenck, there is one personality dimension that characterizes ‘anxiety-type feelings’, namely neuroticism which is associated with anxiety. The research was conducted using a cross-sectional study method with the communibiology paradigm which has the premise that biological factors play a role in determining individual communication behavior. Using simple random sampling, total of 49 Family Planning Counselors in East Java, Indonesia have neuroticism personality tendencies through the Eysenck Personality Questionnaire Short Form. Meanwhile, the Personal Report of Communication Apprehension was used to measure the level of communication apprehension. The results showed that neuroticism was positively correlated with communication apprehension (r = 0.423). This finding can be explained by cortical emotional processing processes, including emotional regulation, cognitive appraisal, and heightened sensitivity to perceived social threats, which are commonly associated with individuals high in neuroticism. This study contributes to the growing body of research on personality by encouraging further exploration of how personality traits interact with communication-related psychological variables.